Toward Higher Laws: Henry David Thoreau’s Concept of Animal Rights in Walden - Tang Wei (Britain International for Academic Research (BIAR-Publisher), 2021)
Though living in the age of Industrialization when the concept of anthropocentricism was prevalent and not a hardcore vegetarian, Thoreau challenged the anthropocentric view of human being’s condescending superiority over animals in Walden. Not only does Thoreau view non-human animals as subjects possessing their own consciousness and sentience, he also regards a consummation of one’s spirituality involves admitting and understanding of one’s inner animality so as to inhibit his savage instinct to hunt or kill animals for food, on the grounds that animals are sentient to feel pain and sufferings and animal food is both unclean and degenerated. Therefore, Thoreau’s humanity to non-human animals inspires and will inspire his modern readers to show more respect for non-human animals and lead them to aspire for a higher stage in their spiritual development. It is in this sense that Thoreau’s concept of animal rights in Walden shakes the solid foundation of anthropocentricism and approximates, if not pioneers, the modern concept of animal rights.